Hsp10 nuclear localization and changes in lung cells response to cigarette smoke suggest novel roles for this chaperonin. Issue 10 (October 2014) - Corrao, Simona; Anzalone, Rita; Lo Iacono, Melania; Corsello, Tiziana; Di Stefano, Antonino; D'Anna, Silvestro Ennio; Balbi, Bruno; Carone, Mauro; Sala, Anna; Corona, Davide; Timperio, Anna Maria; Zolla, Lello; et al.
Abstract : Heat-shock protein (Hsp)10 is the co-chaperone for Hsp60 inside mitochondria, but it also resides outside the organelle. Variations in its levels and intracellular distribution have been documented in pathological conditions, e.g. cancer and chronic obstructive pulmonary disease (COPD). Here, we show that Hsp10 in COPD undergoes changes at the molecular and subcellular levels in bronchial cells from human specimens and derived cell lines, intact or subjected to stress induced by cigarette smoke extract (CSE). Noteworthy findings are: (i) Hsp10 occurred in nuclei of epithelial and lamina propria cells of bronchial mucosa from non-smokers and smokers; (ii) human bronchial epithelial (16HBE) and lung fibroblast (HFL-1) cells, in vitro, showed Hsp10 in the nucleus, before and after CSE exposure; (iii) CSE stimulation did not increase the levels of Hsp10 but did elicit qualitative changes as indicated by molecular weight and isoelectric point shifts; and (iv) Hsp10 nuclear levels increased after CSE stimulation in HFL-1, indicating cytosol to nucleus migration, and although Hsp10 did not bind DNA, it bound a DNA-associated protein.